TREN RUMAH KAYU TRADISIONAL JAWA PADA BANGUNAN KOMERSIL DI BALI - Persada, Nyoman Gema Endra; Puspita Giri, Kadek Risna; Ariyani, I Gusti Ayu Dwiyanti (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
Bali as a global tourist destination continues to experience massive architectural developments. Wooden houses from outside Bali are now increasingly standing on land plots in Bali, both for sale and purchase or directly as commercial accommodation. Why does this phenomenon occur? What is the opportunity for local Balinese buildings to this phenomenon? This paper tries to dissect this phenomenon through a qualitative method where the researcher makes direct observations in the field and conducts interviews with several wooden house industry players in Bali. The various wooden houses that are most prevalent in Bali are Javanese houses such as geladak and joglo. The knockdown system makes it easier to buy and sell wooden houses because of the ease of dismantling pairs of houses to move places and change owners. The older wood material makes it more exotic and increases its selling value, besides that, the old wood material from the previous house is often used as recycled wood to make a new house. The high number of construction workers from Java who work in Bali, including carpenters, is slowly transmitting its characteristics to Bali. Bali's dependence on wood from outside the island, including from Java, has contributed to the rapid expansion of wooden houses from Java to Bali. Traditional Balinese buildings actually have several wooden structures such as a bale bengong / gazebo and barn / jineng. The Balinese wooden house is not as sexy as the Javanese wooden house apart from the above reasons, the bale bengong is small and open (less private), while the jineng is too hot because of its original function as a rice barn.